(untitled) (Agro Productividad, 2022)
Objective: To isolate bacteria from pulque with probiotic potential for animal feed. Design/Methodology/Approximation: Samples were taken from pulque in the municipalities Tlatlauquitepec, Puebla; Otumba and Tequexquináhuac, Estado de México. For the samples, pH, moisture, ash, and protein were determined. The bacteria colonies were isolated and identified morphologically. Gram dyeing and the catalase test were conducted in pre-selected strains from colonies. In the end, strains with probiotic potential, resistance to pH, biliary salts and antimicrobial activity were identified. Results: For pH, moisture, ash, and protein in pulque samples from Tlatlauquitepec, the results were 3.3, 96.17%, 5.98% and 0.352 g 100 mL-1; from Otumba, 3.25, 97.67% and 0.1763 g 100 mL-1; and from Tequexquináhuac, 2.25, 97.55%, 4.65% and 0.1765 g 100 mL-1. Six different strains were isolated (C2, C3 and C4 in Tequexquináhuac; C5 and C6 in Otumba; and C1 in Tlatlauquitepec). It was found that strain C1 could grow in a pH of 3.0 with survival of 84 % and 73% in biliary salts. Study Limitations/Implications: Bacteria from pulque present probiotic characteristics that can be used for animal feed. Findings/Conclusions: Strain C1 grew in pH of 3.0 and showed high percentage of survival, which is why it can be used as probiotic in animal feed.